Effects of beer on the gastric mucosa as determined by endoscopy - Franke, Andreas; Singer, Manfred V. (Beer in health and disease prevention, 2009)
It is clinically well known that alcohol consumption, especially in excess, may cause acute gastrointestinal bleeding and hemorrhagic gastritis. Induction of hemorrhagic lesions was endoscopically proven for pure ethanol solutions in concentrations between 40% and 80% by several studies. However, the data on the effect of alcoholic beverages and their corresponding ethanol concentrations is rare. Only in one study the effect of beer, some other alcoholic beverages and their appropriate control solutions (4% and 10% v/v ethanol and isotonic saline) was endoscopically examined in humans. Additionally, the time-dependent course of potential lesions was determined. According to these results, beer induces gastric mucosal injury in healthy non-alcoholic volunteers that are endoscopically detectable 30, 60 and 240 min after the application. After 24h those lesions are completely healed. However, the injury by 4% ethanol is significantly stronger than that of beer. Beer may contain ingredients that protect the gastric mucosa against the damaging action of ethanol.